Affectivity and physical habits in adolescents: A systematic review - Huerta-Ojeda, Álvaro Cristian; Riquelme-Vera, Gerardo; Yeomans-Cabrera, María Mercedes (Universidad y Salud, 2021)
Introduction: Affectivity has a fundamental role in educational systems’ training process. However, there are no updated studies that show the different socio-affective agents used in the creation of physical habits in the child and adolescent population in school systems. Objective: To review and analyze previously published research that studied the influence of affectivity on children and adolescents’ physical habits in school systems. Materials and methods: A systematic review was conducted with articles published between 2010 and 2020, which connected affectivity and physical habits. The electronic search was performed through Web of Science, Scopus, and Scielo databases. All articles that studied the influence of affectivity on the population’s physical habits were included. Results: Three studies that analyzed the influence of affectivity on children and adolescents’ physical habits were found. Conclusions: At the end of the systematic review, it was demonstrated that there is a significant relationship between affectivity and the physical habits in child and adolescent populations. It was also possible to observe that this influence, positive or negative, determines the child and adolescent population’s interest in physical activity and sports in adult life.